Counseling on the use of the herbal plant red ginger (Zingiber officinale Rosc. var. rubrum) to make instant granules - Ayu Gita Hamdani; Lia Hawangi Sukma Taryadi; Iqbal Bagus Prayogo; Lela Sulastri; Didin Ahidin (Universitas Muhammadiyah Magelang, 2023)
Romangloe Village is situated in the Bontomarannu District, Gowa Regency. With its hilly terrain and expansive areas, the majority of the population earns their livelihood through farming and plantations. Consequently, a group of women known as the Women Farmers Group (KWT) has been formed, dedicated to cultivating and preserving Green Houses for growing various vegetables commonly consumed on a daily basis. Among the crops cultivated is red ginger, yet the community has not fully tapped into its potential for achieving a higher market value. The goal of this empowerment initiative is to enhance the insight of the KWT, enabling them to produce processed ginger with an extended shelf life and increased market value. The methodology involves providing assistance in the production of instant ginger granules and counseling on the benefits of both ginger and instant ginger granules. The outcome of this empowerment effort is a heightened understanding of red ginger and the ability to produce processed red ginger.